Computation Of Fuzzy Analytic Hierarchy Process (FAHP) Using Matlab Programming In Sustainable Supply Chain - Mohamed Noor, Ahamad Zaki; Md Fauadi, Muhammad Hafidz Fazli; Zulkifli, Nur Zul Hafiq; Abdul Basit, Muhamad Naqib; Jafar, Fairul Azni; Mohamad, Nor Rashidah (Science Publishing Corporation, 2018)
Fuzzy Analytic Hierarchy Process (FAHP) is a well-known method which is currently used by many researchers all around the world. However, the problem lies where the steps are lengthy and consumes time. This paper does the purpose to share a method where Decision Makers (DM) can reduce error or any mistakes while manual compute. A MATLAB programming is develop and field of sustainable supply chain is use as experiment purpose. There is one out of four criteria need to be selected by using FAHP. The criteria are cost, quality, delivery time and supplier distance. Both methods are done simultaneously and the answers were recorded. The percentage accuracy shows 100% for every step showing there is no error and the answers are the same if MATLAB is applied. Final answers for both shows that quality is the highest criterion to be selected based on the weightage.